1987
DOI: 10.1295/polymj.19.231
|View full text |Cite
|
Sign up to set email alerts
|

13C NMR Study on the Distribution of Substituent Groups on Trihydric Alcohol Units in Cellulose Xanthate

Abstract: ABSTRACT:An attempt was made to investigate 13 C{ 1 H} NMR spectra for cellulose xanthate (CX) in sodium hydroxideiD 2 0 mixture and to assign NMR peaks of CX by applying the DEPT method and by inspecting the change in NMR spectra with ripening time. Based on NMR analysis a direct method is proposed for determining the probability of substitution at hydroxyl groups located at C 2 , C 3 , and C6 positions in trihydric glucopyranose unit (k=2, 3, and 6). The difference in ((fk)) between CXs prepared by the gas-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…In order to evaluate {fk)> for not-fully substituted CA with good accuracy, the reliable assignment of the abovementioned 12 peaks is very prerequisite because rough classification of these peaks into three parts (carbonyl at C 2 , C 3 , and C 6 ) made by Kamide 13 and Kamide and his collaborators 5 came to the same conclusion that CA samples with the same {F)>, prepared under different conditions, had different degrees of water solubility, and discussed the relations between {fk)> by NMR method and the water solubility for CA: CA having {f 2 )> {f 3 )> {f 6 )> (i.e., CA with uniformly distributed acetyl groups) dissolves almost completely in water at room temperature in the range of {F)> from 0.6 to 1.0. In contrast to this, CA having {f 6 )> {f 2 )> + {f 3 )> (i.e., CA with acetyl groups highly selectively located at C 6 position) is little better than insoluble in water over the entire {F)> range. In addition, Kamide et al 5 demonstrated that CA having {f2 )> {f 3 )> {f 6 )> easily dissolves completely in dimethylacetamide (DMAC) at room temperature irrespective of {F)>, if {F)> is at least larger than 0.6, and CA having {f6 )> {f2 )> + {f 3 )> dissolves only partly in DMAC even at 80°C in the same {F)> range.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…In order to evaluate {fk)> for not-fully substituted CA with good accuracy, the reliable assignment of the abovementioned 12 peaks is very prerequisite because rough classification of these peaks into three parts (carbonyl at C 2 , C 3 , and C 6 ) made by Kamide 13 and Kamide and his collaborators 5 came to the same conclusion that CA samples with the same {F)>, prepared under different conditions, had different degrees of water solubility, and discussed the relations between {fk)> by NMR method and the water solubility for CA: CA having {f 2 )> {f 3 )> {f 6 )> (i.e., CA with uniformly distributed acetyl groups) dissolves almost completely in water at room temperature in the range of {F)> from 0.6 to 1.0. In contrast to this, CA having {f 6 )> {f 2 )> + {f 3 )> (i.e., CA with acetyl groups highly selectively located at C 6 position) is little better than insoluble in water over the entire {F)> range. In addition, Kamide et al 5 demonstrated that CA having {f2 )> {f 3 )> {f 6 )> easily dissolves completely in dimethylacetamide (DMAC) at room temperature irrespective of {F)>, if {F)> is at least larger than 0.6, and CA having {f6 )> {f2 )> + {f 3 )> dissolves only partly in DMAC even at 80°C in the same {F)> range.…”
mentioning
confidence: 89%
“…In fact, experimental results reported on iFimn:» of cellulose xanthate differ depending on researchers who carried out, unexceptionally, the conversion of the xanthate group into a more stable form through very complicated chemical reactions. 3 Wu, 8 and Clark and Stephenson 9 proposed methods for estimating molar fractions of 2,3,6-tri-, 2,6-di-, 3,6-di-, and 6-mono-substituted glucopyranose units of cellulose nitrates, whose C 6 position was fully substituted (i.e., if6 ))= 1) from their 13 C NMR spectra. However their methods cannot be applied to cellulose nitrate whose hydroxyl group at the C 6 position is not fully substituted.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…From systematic analysis on 1 H and 13 C NMR spectra of sodium cellulose sulfate,4 cellulose acetate (CA), 5 -7 sodium carboxymethylcellulose,8 sodium cellulose xanthate (CX), 9 carboxyethylcarbamoylethylcellulose 10 and cyanoethylcellulose, 11 Kamide, Okajima, and their coworkers elucidated <(fk)) (k =2, 3,6), correlation <(fk)) with some physical and physilogical properties. Wu, 12 Clark and Stephenson, 13 and Miyamoto et al 14 estimated, from NMR spectra, <(fk)) of cellulose nitrate and CA.…”
mentioning
confidence: 99%
“…Kamide and his coworkers evaluated, mainly using NMR method, and for various cellulose derivatives including cellulose acetate (CA), 2 · 3 cellulose sulfate, 4 -6 sodium carboxymethyl cellulose (NaCMC), 6 cellulose xanthate, 7 and carboxyethyl carbamoylethyl cellulose, 8 and demonstrated that some physical and physiological properties are not only a single function of but also functions of (k=2, 3, and 6) and Kowsaka et a!. 9 determined average molar fractions for eight kinds of unsubstituted, partially and fully substituted AHG units of cellulose acetate samples by establishing full assignments of all carbonyl peaks of 13 C{ 1 H} NMR spectra.…”
mentioning
confidence: 99%